Lack of penetration of amikacin into saliva of tuberculosis patients. Issue 1 (11th January 2018) - van den Elsen, Simone H.J.; Akkerman, Onno W.; Huisman, Justine R.; Touw, Daan J.; van der Werf, Tjip S.; Bolhuis, Mathieu S.; Alffenaar, Jan-Willem C.
In the 2016 update of the World Health Organization treatment guideline for drug-resistant tuberculosis (TB), a shorter multidrug-resistant TB regimen was proposed because of its higher treatment outcomes [1]. However, therapeutic drug monitoring (TDM) is an excellent method to improve clinical outcomes as well and its practice is on the rise [2]. A well-known side-effect of group B injectable anti-TB drugs ( e.g . amikacin) is ototoxicity [3]. TDM could also be a solution to minimise side-effects by lowering the drug exposure [4]. In the study byvan Altena et al. [5], TDM was practised using the ratio of peak concentration ( C max ) to minimal inhibitory concentration (MIC) and this resulted in a reduction in patients with hearing loss. Saliva is considered as an alternative matrix for TDM because it is easy, noninvasive and more patient friendly to sample [6]. Studies found a limited penetration of gentamycin and tobramycin into saliva [7], while detectable levels of amikacin in saliva of neonates were reported [8]. Given the low penetration of aminoglycosides into saliva and interest in C max for TDM of amikacin, our objective was to study whether the salivary C max of amikacin is measurable and useful in salivary TDM. Salivary C max TDM of amikacin was not feasible in TB treatment due to the very low penetration into saliva http://ow.ly/d6v230h0bWG